Expert patient perspectives on radiotherapy: a phenomenological comparison. Issue 2 (20th February 2017) - Carmichael, M.; Bridge, P.
Abstract: Background: Patient involvement in health profession student training is becoming more common and includes clinical case studies, informing curriculum development and active teaching in dedicated patient experience sessions. Despite a growing evidence base supporting patient involvement, there is little published data concerning motivation for involvement. A qualitative study was performed to provide narrative relating to patient experiences in expert patient sessions on an undergraduate radiation therapy course. Methods: A phenomenological approach utilised semi-structured interviews with two expert patients from different backgrounds. A common set of questions were used for each participant. Interviews were digitally recorded and transcribed before thematic coding. Results: Both participants identified areas of similarity as well as key difference in their experiences. Both had different levels of public speaking experience as well as different levels of knowledge relating to radiation therapy treatment. Both found the initial session emotional but ultimately enjoyed the process and found it cathartic. Conclusion: The patients enjoyed this experience and identified clear value of the teaching for themselves and the students. Previous public speaking or clinical experience seemed to have limited impact on patient experience and suggested the vulnerability of the situation. Both had different perspectives of their fellow patients and their role in the healthcare partnership. These findings indicate the value of ensuring students have access to a range of perspectives from different patients.